A Conceptual Review On Strategic Human Resources Management And Planning In Non Profit Motive Organization - Shah, Gyanendra Bikram (Journal of Business and Social Sciences, 2018)
The nonprofit and public sectors are facing significant numbers of impending retirements from the traditionalists and baby boomers in their workforces. In an effort to retain the knowledge base of an agency or to better serve its clients, some organizations have developed creative ways to encourage retirement-eligible employees to remain on the job. Public and nonprofit organizations are driven by the knowledge and skills their employees possess. It is shortsighted for elected officials, board members, funders, executives, and other agency leaders to dismiss the importance of SHRM. As important, organizations must reinforce the importance of human capital and the contribution that knowledge management makes to the effective delivery of services.